Nepal–India Relationship After The Rise of Modi - Kandel, Ishwori Prasad (Historical Journal, 2020)
This paper has attempted to define Nepal, being a sovereign country would like to deal with India on an equitable basis. Geographically, culturally and economically, Nepal is closer to India. Nepal also realizes that it can’t ignore its southern neighbor India. The Republic of India and the Federal Democratic Republic of Nepal initiated their relationship with the 1950 Indo-Nepal Treaty of Peace and Friendship and accompanying secret letters that defined security relations between the two countries, and an agreement governing both bilateral trade and trade transiting Indian territory. The Indo-Nepal border is open; Nepalese and Indian nationals may move freely across the border without passports or visas and may live and work in either country. However, Indians aren’t allowed to own land-properties or work in government institutions in Nepal, while Nepalese nationals in India are allowed to work in Indian government institutions (except in some states and some civil services the IFS, IAS, and IPS). After years of dissatisfaction by the Nepalese government, India in 2014, agreed to revise and adjust the treaty to reflect the current realities, however, the modality of adjustment hasn’t been made clear by either side. Due to geographical proximity, socio-cultural affinity and economic dependence of Nepal, India has strong influence on Nepal and its policy decisions. Modi’s first visit to Nepal in August 2014 as part of his ‘neighbourhood first’ policy was highly successful. He was the first foreign leader to address the Constituent Assembly - the body tasked with drafting Nepal’s new constitution. His remarks drew widespread praise from all Nepalese political parties and seemed to promise a new beginning in India–Nepal relations. Minister Narendra Modi had expressed its displeasure at Nepal’s constitution, a position made clear in a series of statements issued by Ministry of External Affairs (MEA) in New Delhi. Citing MEA sources, Indian Express even circulated a seven-point demand for amendments to the constitution, within days of its promulgation. With the election of nationalistic leader K P Oli as prime minister in Nepal, the rift between Delhi and Kathmandu was widened, and lead to a massive humanitarian crisis, as shortages of fuel, medicines, and essential supplies become acute across Nepal, with no sign of reconciliation in sight.